2024
DOI: 10.1029/2023jd039387
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Evapotranspiration Over China From 1982 to 2020: Consistency of Multiple Data Sets and Impact of Input Data

Yuna Mao,
Jiaxin Bai,
Guocan Wu
et al.

Abstract: Due to limited direct measurements, regional or global terrestrial evapotranspiration (ET) is generally derived from a combination of meteorological and satellite observations. Although the inhomogeneity of the observed climate data has been widely reported, its impact on the calculated ET has not been adequately quantified. This study aimed to calculate ET using the modified Penman‐Monteith (MPM) model with raw and homogenized meteorological data. Additionally, we compared the calculated ET with those estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 190 publications
(478 reference statements)
0
1
0
Order By: Relevance
“…We use the Global Land Evaporation Amsterdam Model (GLEAM) V3.7 ET product (Martens et al, 2017) as reference, which has been shown to exhibit relatively high accuracy (Jia et al, 2022;Mao et al, 2024). GLEAM ET data set is available on a 0.25°regular grid and at daily temporal resolution.…”
Section: Model and Datamentioning
confidence: 99%
“…We use the Global Land Evaporation Amsterdam Model (GLEAM) V3.7 ET product (Martens et al, 2017) as reference, which has been shown to exhibit relatively high accuracy (Jia et al, 2022;Mao et al, 2024). GLEAM ET data set is available on a 0.25°regular grid and at daily temporal resolution.…”
Section: Model and Datamentioning
confidence: 99%